When ties don't bind: smuggling effects, bazaars and regulatory regimes in postrevolutionary Iran - Erami, Narges; Keshavarzian, Arang (Economy and society, 2015)
This paper examines how participation in smuggling restructures existing commercial regulatory systems and subjectivities. It does so through an analysis of the illicit commercial practices that mushroomed in postrevolutionary Iran and the ambivalent participation of established merchants (bazaaris) in the import and export of commodities through these circuits during the 1979-2005 era. Following two independent research projects on the Tehran and Qum bazaars, we adopt a multidisciplinary and relational approach to bazaars and smuggling to decipher the multiple logics. This process is assembled through networks of established bazaaris, new commercial actors, far-flung transnational buyers and diverse state officials, who both regulate trade and facilitate exchanges that are at times interpreted as smuggling by the participants themselves. Building on the growing literature on smuggling in cultural anthropology and political economy, our account demonstrates how commodities travel through channels that ultimately transgress categories such as licit and illicit, state and society, and 'honorable bazaari' and 'smuggler'. The postrevolutionary Iranian regime is a case that challenges us to examine this quasi-formal economy in the context of an institutionalized and centralized state that has adopted both state-led and neoliberal economic policies. It also forces us to situate the phenomenon of smuggling within the context of existing commercial networks and moral orders. We further reveal how bazaaris have been subjects of and subjected to the hybrid commercial order, which has both displaced the social networks that underpin bazaaris' communal obligations and norms and cast doubt on the merchants' claim to ethical standing in the eyes of one another, and left them vulnerable to criticism by leaders of the Islamic Republic.